2012
DOI: 10.4103/2045-080x.106242
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and perceived outcomes of complementary and alternative medicine use in hospitalized British patients

Abstract: Objectives:This study aimed to investigate the prevalence and perceived outcomes of complementary and alternative medicine (CAM) use in secondary care patients and to find out determinants for CAM utilization and perceived effectiveness and side-effects. Materials and Methods: Patients who met the eligibility criteria in this cross-sectional study were interviewed using a semi-structured questionnaire. Patients' medications and relevant details were verified from the medical notes. A logistic regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
3
4
0
Order By: Relevance
“…Although no CM was delivered by the hospital during the study period, still one‐tenth of patients reported taking CM during their hospital stay. This prevalence is in agreement with one study conducted among inpatients in Denmark and another conducted in England . Self‐medication during hospitalisation should also be searched for, especially herbal medicine which was among the most CM used 2 months before and during hospitalisation in our study.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Although no CM was delivered by the hospital during the study period, still one‐tenth of patients reported taking CM during their hospital stay. This prevalence is in agreement with one study conducted among inpatients in Denmark and another conducted in England . Self‐medication during hospitalisation should also be searched for, especially herbal medicine which was among the most CM used 2 months before and during hospitalisation in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Lifetime CM use among hospitalised patients was comparable to other studies conducted in England (90%), Australia (90%), and Scotland (68%), but considerably higher than among the Swiss population (49%) . This discrepancy could be partially explained by differences in the characteristics of the populations surveyed (older age, more chronic diseases among hospitalised patients) and the definition of CM.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations